2022
DOI: 10.1007/978-3-030-98260-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Intersection Focused Situation Coverage-Based Verification and Validation Framework for Autonomous Vehicles Implemented in CARLA

Abstract: Autonomous Vehicles (AVs) i.e., self-driving cars, operate in a safetycritical domain, since errors in the autonomous driving software can lead to huge losses. Statistically, road intersections which are a part of the AVs operational design domain (ODD), have some of the highest accident rates. Hence, testing AVs to the limits on road intersections and assuring their safety on road intersections is pertinent, and thus the focus of this paper. We present a situation coverage-based (SitCov) AV-testing framework … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…They build upon their previous works [40,45,28]. Tahir and Alexander [39] propose an ontology that focuses on intersections due to their high collision rates. They show that their scenarios can be executed in simulation, while focusing on changing weather conditions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They build upon their previous works [40,45,28]. Tahir and Alexander [39] propose an ontology that focuses on intersections due to their high collision rates. They show that their scenarios can be executed in simulation, while focusing on changing weather conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Ontology available Fuchs et al [16] 2008 --✓ ---Hummel [25] 2010 -✓ ----Hülsen et al [26] 2011 ✓ ✓ ----Armand et al [1] 2014 ------Zhao et al [47] 2017 -✓ ---✓ Bagschik et al [5] 2018 ✓ -----Chen and Kloul [13] 2018 ✓ -----Huang et al [24] 2019 ✓ -----Menzel et al [30] 2019 ✓ ✓ -✓ --Li et al [29] 2020 ✓ ✓ -✓ --Tahir and Alexander [39] 2022 ✓ --✓ --Hermann et al [23] 2022…”
Section: Corner Case Categorizationmentioning
confidence: 99%
“…Hawkins et.al [11] and Tahir and Alexander [18] evaluated situation coverage approach that is łCan a situation generation testing method based on situation coverage approach outperform a randomly generation one in terms of fault detection?ž . Though the task environment of [11] and [18] were different with different seeded faults, they got almost same result.…”
Section: Introductionmentioning
confidence: 99%
“…Hawkins et.al [11] and Tahir and Alexander [18] evaluated situation coverage approach that is łCan a situation generation testing method based on situation coverage approach outperform a randomly generation one in terms of fault detection?ž . Though the task environment of [11] and [18] were different with different seeded faults, they got almost same result. They concluded that the situation coverage does not achieve significant benefits over random situation generation but coverage directed generation does cover a greater proportion of the situation space in the same amount of compute time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation